Council on Resident Education in Obstetrics and Gynecology In-Training Examination Results: Identifying Predictive Factors. (October 2015) - Lingenfelter, Brandon M.; Forstein, David A.; Jiang, Xuezhi; Minassian, Shahab S.; O'Sullivan, David; Schnatz, Peter F.
Abstract : BACKGROUND: The Council on Resident Education in Obstetrics and Gynecology (CREOG) In-Training Examination (ITE) was designed to serve as a tool to provide feedback on resident progress along with training program strengths and weaknesses. OBJECTIVE: The objective of this study was to identify predictive factors for success on American Board of Obstetrics and Gynecology (ABOG) Written Examination using CREOG ITE scores. METHODS: CREOG ITE and ABOG written examination results collected from 2002 to 2012, inclusive, from Reading Hospital and Greenville Health System residents who took the CREOG ITE exam for 4 years. Data were analyzed using logistic regression to identify key factors in predicting ABOG written examination outcomes. Categorical data were analyzed using χ 2 . RESULTS: Seventy-one residents were included for analysis, of whom 68.9% were female. Gender differences existed. For women, a low score starting in postgraduate year (PGY)-1 was correlated with ABOG failure ( P <.001), but it was not associated in men ( P =NS) until PGY-3. Results showed that while each year's score contributed to the chance of pass–fail, the contribution increased each year. For every point increase in year 4 examination score, chances of passing increased by 21.5% ( P =.001). Calculations using all 4 years resulted in an area-under-the-curve (AUC) of 0.920, significantly better ( P <.001) than the null hypothesis of 50%. CONCLUSION: Results indicate that the score of each subsequent PGY is more important than the previous PGY's score. CREOG ITE scores could be a useful tool for identifying residents requiring structured interventions.